Oral and Injection Hormonal Contraceptives Uptake and Their Risk to Breast Cancer: A Meta-Analysis - Utami, Dian Asih Ning; Murti, Bhisma; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2022)
Background: Breast cancer cases are the biggest contributor to death in women in the world. One of the risk factors is injectable hormonal contraceptives and pills. Injectable hormonal contraceptives and pills contain synthetic hormones progesterone and estrogen that trigger breast cancer, due to an increase in the content of these hormones in the body, this results in an opportunity to experience uncontrolled cell division resulting in gene mutations in the breast gland. The purpose of this study was to analyze the effect of the use of injectable and pill hormonal contraceptives on the incidence of breast cancer using a meta-analysis study.Subjects and Method: This research is a systematic review and meta-analysis using PRISMA flowchart diagram guidelines. The article search process was carried out between 2015-2022 using databases including Google Scholar, PubMed, Science Direct and Springerlink. The keywords used in the database search were